Application of small molecule FPR1 antagonists in the treatment of cancers - Ahmet, Djevdet S.; Basheer, Haneen A.; Salem, Anwar; Lu, Di; Aghamohammadi, Amin; Weyerhäuser, Patrick; Bordiga, Andrea; Almeniawi, Juman; Rashid, Sabah; Cooper, Patricia A.; Shnyder, Steven D.; Vinader, Victoria; et al. (Scientific reports, 2020)
The formylpeptide receptor-1 (FPR1) is a member of the chemotactic GPCR-7TM formyl peptide receptor family, whose principle function is in trafficking of various leukocytes into sites of bacterial infection and inflammation. More recently, FPR1 has been shown to be expressed in different types of cancer and in this context, plays a significant role in their expansion, resistance and recurrence. ICT12035 is a selective and potent (30 nM in calcium mobilisation assay) small molecule FPR1 antagonist. Here, we demonstrate the efficacy of ICT12035, in a number of 2D and 3D proliferation and invasion in vitro assays and an in vivo model. Our results demonstrate that targeting FPR1 by a selective small molecule antagonist, such as ICT12035, can provide a new avenue for the treatment of cancers.